2018
DOI: 10.1007/s10548-017-0617-4
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Somatosensory Evoked Potentials of the Fingers: Limitations and Clinical Potential

Abstract: In searching for clinical biomarkers of the somatosensory function, we studied reproducibility of somatosensory potentials (SEP) evoked by finger stimulation in healthy subjects. SEPs induced by electrical stimulation and especially after median nerve stimulation is a method widely used in the literature. It is unclear, however, if the EEG recordings after finger stimulation are reproducible within the same subject. We tested in five healthy subjects the consistency and reproducibility of responses through boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…For the able-bodied individuals, the estimated cortical sources and dynamic information flow are found only at the sensorimotor areas contralateral to the finger stimulation. This result is consistent with previous electro-neurophysiological studies (Jamali and Ross, 2013 ; Porcaro et al, 2013 ; Kalogianni et al, 2018a ), showing that the somatosensory information is processed by brain regions predominantly contralateral to the stimulated hand. Conversely, in chronic hemiparetic stroke participants, the activation of brain activity occurs in both hemispheres, with information flow transmitted from the contralateral (ipsilesional) to the ipsilateral (contralesional) hemisphere in the time period between P50 and N100 whereas in control participants cortical activity stays over the contralateral hemisphere.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For the able-bodied individuals, the estimated cortical sources and dynamic information flow are found only at the sensorimotor areas contralateral to the finger stimulation. This result is consistent with previous electro-neurophysiological studies (Jamali and Ross, 2013 ; Porcaro et al, 2013 ; Kalogianni et al, 2018a ), showing that the somatosensory information is processed by brain regions predominantly contralateral to the stimulated hand. Conversely, in chronic hemiparetic stroke participants, the activation of brain activity occurs in both hemispheres, with information flow transmitted from the contralateral (ipsilesional) to the ipsilateral (contralesional) hemisphere in the time period between P50 and N100 whereas in control participants cortical activity stays over the contralateral hemisphere.…”
Section: Discussionsupporting
confidence: 93%
“…Index fingers of both hands were stimulated with a randomized order in healthy controls and stroke patients with bipolar stimulation using a battery-powered electrical stimulator (Micromed, Brain quick, Treviso, Italy). The anodal electrode (size 1 cm) was placed on most distal phalange and cathode on the second distal phalange with an inter-electrode distance of ~1 cm (Kalogianni et al, 2018a ). This placement is chosen to reduce the likelihood of anodal block (Cruccu et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our results are in line with tactile MEG and EEG studies that have reported either overlapping locations of somatosensory evoked field potentials of fingers (Baumgartner et al, 1993;Kalogianni et al, 2018;Schaefer et al, 2002;Simões et al, 2001) or that have managed to discriminate the activations related to mainly the index finger and thumb (Barbati et al, 2006;Nierula et al, 2013;Rossini et al, 2001Rossini et al, , 1998. However, some MEG studies have found somatotopic cortical organization to tactile stimulation of the fingers (Nakamura et al, 1998).…”
Section: Ckc Source Locations Were Concentrated On the Hand Region Ofsupporting
confidence: 91%
“…[8][9][10] Finger stimulation evoked somatosensory potentials could theoretically be an approach to study somatosensory processing, however, may not be recommend due to the lack in reliability. 11 Cortical rebound responses in the beta band of the affected hemisphere measured with magnetoencephalography during manual passive finger movements, were found to correlate with the initial severity and recovery of motor activity as measured with the box and block test at 1 and 12 months poststroke. 12 Joint position perturbations act as an external excitation signal for the proprioceptive system, primarily the Golgi tendon organs and muscle spindles, providing an interesting approach to study sensorimotor processing in severely affected patients.…”
mentioning
confidence: 95%